Nitric oxide synthase phosphorylation in fetoplacental endothelium is enhanced by agonism of Piezo1 mechanosensor in small for gestational age babies - L C Morley; M Debant; H J Gaunt; N A B Simpson; D J Beech (Bioscientifica, 2023)
Friction caused by blood flowing across cells that line blood vessels (endothelial cells) activates sensors of mechanical force. This produces nitric oxide (NO) which widens placental blood vessels, enabling more blood flow to the baby. This study sought to determine whether the mechanical sensor, Piezo1, is important for NO production in fetoplacental endothelial cells (FpECs) and whether the steps in this pathway are different in small for gestational age (SGA) babies, where placental blood flow is often altered. We showed that in healthy FpECs, blood flow increased NO signalling. We suggest that in SGA babies, FpECs have an increase in baseline levels of NO signalling, suggestive of a compensatory drive. Treating healthy and SGA cells with a Piezo1 chemical activator, Yoda1, upregulated NO signalling. This shows that Piezo1 is linked to NO and that in SGA, FpECs have the capacity to further increase NO. Further research will establish whether Piezo1 enhancement leads to increased blood flow in the placenta. If so, Piezo1 could be a new target for developing treatments to prevent poor growth of babies in the womb.